Az elitoktatástól a tömegoktatásig (felsőoktatás Franciaországban 1953–1990) - Kiss, Andrea (Gerundium, 2017)
From Elite Higher Educational Systems to Mass Education (Higher Education in France 1953– 990). The french university sytsem is unique in Europe. It is divided between public and private higher educational sectors. This paper aims to identify tensions and  difficulties arised by the higher educational expansion in the french higher educational system.It focuses specifically on the increase in the number of the student and the trends of the expansion after the second world war up to 1990. The introduction of the Bologna system was followed by a large wave of national and foreign students willing to enroll French universities. The significant rise in the number of students led to manifold infrastructural problems. However, the transition from the elit to the mass education not only rised problems but also generated solutions. Seen in this light and based on the rate of enrollment and gender data this study intends to highlight techniques of problem solving in higher educational setting.